1986
DOI: 10.1007/bf02173358
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the endothelium of human donor corneas by induced dilation of intercellular spaces and trypan blue

Abstract: The endothelium of 30 pairs of human cadaver corneas was stained by trypan blue and the intercellular spaces were visualized by induced dilation prior to corneal culture. Trypan blue staining and induced dilation of intercellular spaces by 0.9% and 0.45% NaCl were found to be atraumatic. Only a fraction of damaged cells were stained by trypan blue. Endothelial cell losses in culture did not correlate with the number of trypan-blue stained cells, the post-mortem time, or donor age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Since the endothelial cell borders are inadequately visible in organ culture medium, the cells are swelled by hypotonic solutions that render the cell borders clearly visible within a few seconds. Cell swelling can be achieved by hypotonic sodium chloride solution, hypotonic balanced salt solution (BSS), or hypotonic sucrose solution [12,18]. Sucrose solution (1.8%) is commercially available for this purpose and is used by numerous European cornea banks.…”
mentioning
confidence: 99%
“…Since the endothelial cell borders are inadequately visible in organ culture medium, the cells are swelled by hypotonic solutions that render the cell borders clearly visible within a few seconds. Cell swelling can be achieved by hypotonic sodium chloride solution, hypotonic balanced salt solution (BSS), or hypotonic sucrose solution [12,18]. Sucrose solution (1.8%) is commercially available for this purpose and is used by numerous European cornea banks.…”
mentioning
confidence: 99%
“…The authors revealed that TB (0.06%) dye-assisted capsulorhexis was successfully completed in all eyes and the patients were followed up at day 1, day 7, and one and three months postoperatively. Also, some studies found good biocompatibility at incubation times of up to 15 min and concentrations up to 0.40%, indicating that TB is safe for corneal endothelial cells (3,4,15,(18)(19)(20)(21) . Chung et al also evaluated the safety of TB 1% for assisting visualization of the anterior capsule during phacoemulsification of a mature cataract, and found it to be safe (22) .…”
Section: Resultsmentioning
confidence: 99%
“…The whole procedure is simple and accurate, with no effect on the graft's viability [9,11,12]. All precautions provided should be taken, of course, against contamination or damage of the endothelial cells during the examination under the microscope.…”
Section: Discussionmentioning
confidence: 99%
“…The use of trypan blue in the examination of donor corneas, after having been first advocated by Stocker et al [7] in 1966, did not become popular. The reason was the danger of contamination or damaging of the endothelial sheet during the different steps of the procedure [9,11,12].…”
Section: Discussionmentioning
confidence: 99%